REPORT: "IMPACT OF DIGITAL LEARNING TOOLS ON STUDENT ENGAGEMENT AND ACADEMIC PERFORMANCE" (Modern education and development, 2024)
The integration of digital learning tools in education has transformed teaching and learning processes, offering diverse resources to enhance student engagement and academic performance. This report examines the impact of these tools through a comprehensive literature review, focusing on recent studies that analyze various factors, including demographics, subject areas, and digital tool types. Findings indicate that interactive and adaptive digital tools foster student engagement by promoting active participation and accommodating different learning styles. Moreover, these tools enhance academic outcomes when effectively integrated into curricula. The report underscores the importance of educator training, regular evaluation of digital resources, and balanced technology use for optimizing learning environments.